Training Needs of Grass-Root Level Extension Worker - Kavita, Kumari; Shekhar, Dibyanshu; Singh, A. K. (Indian Journal of Extension Education, 2017)
The multiplicity of extension systems are under operation in India considering the varied agro-ecological situations under  which farmers reside, besides variations in the resource base of farmers. The extension system envisaged to achieve  desired growth in agricultural sector with pluralistic in nature. Visualizing the need to deploy trained man power at grass  root level for ensuring effective extension, the Government of Bihar state appointed Agriculture Coordinator and Kisan  Salahkar at panchayat level to cater the farmers' information need and to assist the farmers for giving them advantages of  ongoing agricultural developmental programmes. Training needs for grass root level extension personnel can be defined  in terms of gap between job requirement and job performance. During the study the training need was assessed in the  thematic areas like improved agricultural practices, organization and administration, programme development and  execution, communication skill and social system and local leadership with the help of Agriculture Coordinator and Kisan  Salahkar as the sample. The results of the study reveal that perceived training about improved agricultural technology was  very much needed by the 73.33 per cent of the Agriculture Coordinator, whereas 87.79 per cent of Kisan Salahkar were  also showed the same pattern of this responses.
Keywords: Source of information; Training need of extension personnel